EFFECT OF CUTTING KNIVES SPEED AND FEEDING SPEED ON SOME TECHNICAL INDICATORS FOR THE PERFORMANCE OF A LOCALLY MANUFACTURED MACHINE - S. A. Rawdhan,; W. K. El Helew,; M. A. Mayhoub,; M. M. Moustafa, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The experiment was carried out to study some engineering factors for a locally manufactured machine, It cuts agricultural residues to make animal feed , in the workshops of the Agricultural Engineering Department/Faculty of Agriculture/Ain Shams University for the academic year 2021-2022. The effect of three-speed knives cutting speed (1000,1200,1400 rpm) and three-speed feeding speed (0.75,1,1.25 m/s) and the knife cutting angle with two angles (15°.30°) was studied at a knife clearance of 2.5 mm and a moisture content of 5.3%. With an electronic system with sensors to operate the machine and without. Among the technical indicators that have been studied are productivity, cutting power consumption, specific energy, machine operating costs and the thrust power, The results showed that the performance of machine with an electronic system(senser) to a maize chopping  machine is better than a maize chopping machine without In terms of specific energy consumption, machine  operating costs, at constant clearance of 2.5mm and moisture content 5.3% and an optimum knife speed of 1400 with cutting angle (30°), The maize chopping machine with an electronic system (sensor)  of specific energy consumption (0.0027 kw.h/kg), machine operating costs (0.2159 LE/kg) and highest productivity (105,170 kg/hr)  at cutting angle (30°).